HUBUNGAN ANTARA PENGETAHUAN IBU DAN PENGGUNAAN SUMBER AIR DENGAN KEJADIAN DIARE PADA BALITA DI PUSKESMAS SOSIAL PALEMBANG TAHUN 2012 - Dini Kesumah Dini Kesumah (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2013)
ABSTRACT Diarrheal disease is a major cause of morbidity and mortilitas in children throughout the world, which led to a billion event of sickness and 3-5 million deaths annually. Children are the future assets that will continue the development in a country. The research objective was to determine the relationship of mother's knowledge and use of water resources with the incidence of diarrhea in infants in Social Health Center Palembang in 2012. Penenlitian analytic method used in this survey with cross sectional approach in which data - regarding the independent variable (mothers' knowledge and use of water resources) and the dependent variable (incidence of diarrhea) were analyzed using univariate and bivariate and as many as 30 respondents. The research results obtained frequency distribution of respondents who experienced diarrhea as many as (53.3%) and respondents who did not experience diarrhea as many as (46.7%). Frequency distribution of respondents who have less knowledge of as many as (66.7%) and respondents who have a good knowledge of as many as (33.3%). Frequency distribution of respondents who use piped water sources as many as (53.3%), respondents who use water instead of PAM as many as (40.0%) and respondents who use rainwater as much as (6.7%). There is a significant relationship between knowledge of the incidence of diarrhea in infants in Social Health Center Palembang in 2012 (p value = 0.028). There is a significant correlation between the water source with the incidence of diarrhea in infants in Social Health Center Palembang in 2012 (p value = 0.003).). Promotive expected to society, related to the causes of diarrhea should be done continuously by the relevant agencies to improve maternal knowledge about the prevention of diarrhea in children. ABSTRAK Penyakit diare adalah salah satu penyebab utama morbiditas dan mortalitas pada anak diseluruh dunia, yang menyebabkan kejadian sakit dan 3-5 juta kematian setiap tahunnya. Anak merupakan aset masa depan yang akan melanjutkan pembangunan di suatu negara. Tujuan penelitian adalah untuk mengetahui hubungan pengetahuan ibu dan penggunaan somber air dengan kejadian diare pada balita di Puskesmas Sosial Palembang Tahun 2012. Penenlitian ini menggunakan metode survey analitik dengan pendekatan cross sectional dimana data yang menyangkut variable independen (pengetahuan ibu dan penggunaan somber air) dan variabel dependen (kejadian diare) dianalisis secara univariat dan bivariat dan sebanyak 30 orang responden. Hasil penelitian ini didapat Distribusi frekuensi responden yang mengalami kejadian diare sebanyak (53,3%) dan reponden yang tidak mengaiami kejadian diare sebanyak (46,7%). Distribusi frekuensi responden yang memiliki pengetahuan kurang sebanyak (66,7%) dan reponden yang memiliki pengetahuan baik sebanyak orang (33,3%). Distribusi frekuensi responden yang menggunakan somber air PAM sebanyak (53,3°l0), reponden yang menggunakan somber air bukan PAM sebanyak (40,0%) dan responden yang menggunakan air hujan sebanyak (6,7%). Ada hubungan yang bermakna antara pengetahuan dengan kejadian diare pada balita di Puskesmas Sosial Palembang Tahun 2012 (p value = 0,028). Ada hubungan yang beiFnakna antara sumber air dengan kejadian diare pada balita di Puskesmas Sosial Palembang Tahun 2012 (p value = 0,003).). Diharapkan upaya promotif kepada masyarakat, terkait dengan faktor penyebab diare hendaknya dilakukan secara terus menerus oleh instansi terkait untuk meningkatkan pengetahuan ibu tenting pencegahan diare pada anak.